Local Tourism Popularity Recovery Strategy through Influencer Utilization - Ardhendu Talukdar; Mishti Shekhar (Journal of Management and Administration Provision, 2022)
Using influencers is one way to revive interest in visiting the area. Finding influential people on social media with a significant local following or an interest in tourism and the area is a good first step toward this goal. These people of prominence can be approached and encouraged to write or record content (such as blogs, social media posts, or vlogs) about the location, drawing attention to its best features and enticing their audiences to come check it out. Moreover, it is possible to entice influencers to visit the area by providing them with discounts or other perks in exchange for posting about their experiences on social media. A rise in tourism is a possible outcome, as this might raise the profile of the place and pique interest in it.